2021
DOI: 10.3390/app112311360
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Extended Reality Technology for Teaching New Languages: A Systematic Review

Abstract: Much attention has been given to the use of extended reality (XR) technology in educational institutions due to its flexibility, effectiveness, and attractiveness. However, there is a limited study of the application of XR technology for teaching and learning languages in schools. Thus, this paper presents a systematic review to identify the potential benefits and challenges of using XR technology for teaching new languages. This review provides a basis for adopting XR technology for teaching languages in scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Consequently, they are unable to replicate the experience of tradetional learning (Dwivedi et al, 2022 ). Supporting this, it is found that virtual technologies such as virtual reality (VR), augmented reality (AR), extended reality (XR), and mixed reality (MR), do not, on their own, guarantee positive learning results (Marks & Thomas, 2022 ; Tegoan et al, 2021 ) due to issues related to the multisensory experiences of students in terms of teaching content quality and the appropriateness of realistic dynamic interactions. Therefore, the utilization of metaverse technology in education has the ability to enhance the online learning experience and make it simpler for educational service providers to establish virtual classrooms that imitate traditional classrooms (Teng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they are unable to replicate the experience of tradetional learning (Dwivedi et al, 2022 ). Supporting this, it is found that virtual technologies such as virtual reality (VR), augmented reality (AR), extended reality (XR), and mixed reality (MR), do not, on their own, guarantee positive learning results (Marks & Thomas, 2022 ; Tegoan et al, 2021 ) due to issues related to the multisensory experiences of students in terms of teaching content quality and the appropriateness of realistic dynamic interactions. Therefore, the utilization of metaverse technology in education has the ability to enhance the online learning experience and make it simpler for educational service providers to establish virtual classrooms that imitate traditional classrooms (Teng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, VR/AR/MR on its own does not ensure positive learning outcomes [53,54], and factors that affect the effectiveness of VR/AR/MR in education have been well documented in the literature. Based on the presence theory [55] and regulatory focus theory [56], Sun et al [57] found that promotion focus (i.e., the tendency focuses on the positive presence) positively affects students' satisfaction, perceived efficiency, and overall usability perception toward VR-based learning, whereas involvement (i.e., a psychological state that focuses an individual's attention on a coherent set of activities) and promotion focus positively affect students' perceived effectiveness of VR.…”
Section: Vr/ar/mr In Educationmentioning
confidence: 99%
“…Tegoan et al mentioned that although MR could enhance language learning, its effectiveness could be affected by privacy concerns, expensive costs, etc. [54].…”
Section: Vr/ar/mr In Educationmentioning
confidence: 99%
“…The Metaverse embodies a convergence of web technologies, the internet, VR, AR, mixed reality (MR), and extended reality (XR). According to [21], MR fuses the physical and digital worlds to some degree while combining the technologies of VR and AR into one, while XR universally refers to all these immersive technologies [22].…”
Section: Introductionmentioning
confidence: 99%